Supply Chain Planning and Analytics - Feigin, Gerald (Business Expert Press, 2011)
Ebook from IG Library ; Supply chain planning is concerned with making decisions about how many goods to procure, make, and deliver before knowing exactly what the demand for products is going to be -- decisions which must be made with uncertain and dynamic information about future demand, available production capacity, and sources of supply. This book focuses on three interlinked processes -- demand planning, sales and operations planning, and inventory and supply planning -- which can either help a company to achieve its balance between efficiency and responsiveness or, if executed poorly, cause any number of problems. It also explains how analytical tools and methods can be used to make better supply chain planning decisions.